The bacterial flora of the upper respiratory tract of normal rabbits (2002)
The nasal bacterial flora of 108 apparently healthy rabbits housed th aphylococcus aureus were coagulase positive. Other notable bacteria isolated luteus 9%; Escherichia coli 6%; Streptococcus zooepidemicus 4% and Pseudomonas aerugino